Pengantar teori politk / Andrew Heywood; penerjemah, E. Setiyawati, Rahmat Fajar; penyunting, Rianayati Kusmini P. - Heywood, Andrew ; Setiyawati, E. ; Rahmat Fajar ; Rianayati Kusmini P. (Pustaka Pelajar, 2018)
xii, 717 halaman ; 23 cm